Pengaruh Return on Assets, Return On Equity, dan Loan to Deposit Ratio Terhadap Harga Saham pada Perusahaan Perbankan - Wahyudhianty, Alya Salsabiila; Diyani, Lucia Ari (JURNAL MAHASISWA BINA INSANI, 2023)
The Covid-19 pandemic has hampered business activities, making debtors unable to pay loans, resulting in banks experiencing losses and increasing non-performing loans. This influences investors' decisions in investing which will have an impact on banking share prices and financial performance which can be measured using financial ratio analysis. This research aims to determine the influence of Return on Assets, Return On Equity, and Loan to Deposit Ratio on Share Prices in Banking Companies Listed on the Indonesia Stock Exchange for the 2019-2022 period. This research uses quantitative descriptive methods. The sample for this research consisted of 25 banking companies taken using purposive sampling techniques. The data analysis technique used is multiple regression analysis using SPSS 25. The results of this research show that simultaneously Return On Assets, Return On Equity, and Loan to Deposit Ratio have a significant effect on stock prices. Meanwhile, partially Return On Assets and Loan to Deposit Ratio have a negative and significant effect on stock prices. Return On Equity has a positive and significant effect on share prices.